Day 3 Wed, August 07, 2019 2019
DOI: 10.2118/198797-ms
|View full text |Cite
|
Sign up to set email alerts
|

Maximising Oil Recovery in Mature Water Floods Using Automated Pattern Flood Management

Abstract: One of the most significant challenges for extending production life in mature waterflood fields is high water production. Couple with high reservoir heterogeneity, extensive layering and faulting, these fields often developed irregular flood patterns after decades of production which compounded the challenge to optimizing recovery from these fields. The severity of this problem can be seen in the Niger Delta oil fields where there are several matured fields that are producing at high water cut after many year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Unlike analytical ways which have almost fixed areal sweep efficiency according to flood patterns, this tool uses simulation velocity field and inter well connectivity for designing an optimized injection allocation [10].To optimize the sweep efficiency the streamline uses a concept of Time of Flight (TOF) distribution, by which the areal sweep efficiency is easily optimized and enhanced in complex reservoirs to increase oil recovery in the poorly swept areas [11]. In streamline simulation, the computation is done along the streamlines, in contrast to finite-difference simulators that calculate between cells [12]. Although calculation accuracy is lower than that of finite-difference simulators, streamline simulation is faster is faster and give a quick interpretation about the injection-production interaction and the sweep efficiency in large patterns.…”
Section: Egyptian Journal Of Chemistrymentioning
confidence: 99%
“…Unlike analytical ways which have almost fixed areal sweep efficiency according to flood patterns, this tool uses simulation velocity field and inter well connectivity for designing an optimized injection allocation [10].To optimize the sweep efficiency the streamline uses a concept of Time of Flight (TOF) distribution, by which the areal sweep efficiency is easily optimized and enhanced in complex reservoirs to increase oil recovery in the poorly swept areas [11]. In streamline simulation, the computation is done along the streamlines, in contrast to finite-difference simulators that calculate between cells [12]. Although calculation accuracy is lower than that of finite-difference simulators, streamline simulation is faster is faster and give a quick interpretation about the injection-production interaction and the sweep efficiency in large patterns.…”
Section: Egyptian Journal Of Chemistrymentioning
confidence: 99%
“…The inverted 5-spot well pattern and the inverted 9-spot well pattern are widely implemented in the field. Meanwhile, the optimal well pattern and well spacing under different field conditions have been investigated based on machine learning (data-driven modeling) and numerical simulation [10][11][12][13]. But few studies have been reported on the optimization of well pattern and well spacing of the novel scheme proposed by Shengli Oilfield to develop the pressuresensitive low-permeability.…”
Section: Introductionmentioning
confidence: 99%